Analysis of a case of imported tsutsugamushi disease in Shanghai - ZHU Lin; HE Xiaoding (Shanghai yufang yixue)
ObjectiveTo investigate the clinical characteristics and epidemiological history of an imported case of tsutsugamushi disease, and to identify the diagnosis and key points of prevention and control.MethodsThe clinical symptoms, diagnosis and treatment process, and epidemiological data were retrospectively analyzed for a case of tsutsugamushi disease in Changning District. A risk assessment was conducted concurrently.ResultsThe patient had a history of traveling to or living in Xishuangbanna, Yunnan Province, and presented with symptoms such as recurrent high fever, scabbing and peanut-sized lymph node swelling behind the ear, and red rashes on the face and trunk. The patient tested positive for nucleic acid from Orientia tsutsugamushi and was cured after receiving comprehensive treatment. The patient resides in Shanghai, where the likelihood of hosts and vectors being present in winter is low, hence the risk of epidemic transmission was deemed low.ConclusionThe clinical manifestations of tsutsugamushi disease are not typical in the early stages of the disease. Attention should be paid to epidemiological history and specific symptoms of tsutsugamushi disease, and to strengthen health education and promotion efforts for key populations.